Kompetensi dan Motivasi dalam Pelaksanaan Proses Keperawatan - Masri Masri; Marlina Marlina; Hilman Syarif (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the factors related to implementing the nursing process at the Pidie District General Hospital. This type of research is quantitative research with a cross-sectional study design. The results showed a relationship between the competency factor (Î± = 0.000) and a factor with no ties, namely motivation (Î± = 0.545). In conclusion, the competence possessed by nurses simultaneously influences the process of nursing care, and the motivation owned influences nurses in carrying out nursing care. Keywords: Competence, Nurse Motivation, Nursing Process